Analisa Perancangan Sistem Rekomendasi Makanan Untuk Defisit Kalori “Calcraft” Melalui Evaluasi UI UX - Putu Ananda Darma Wiguna,; Luh Gede Astuti, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
This research raises issues related to unbalanced diets in modern society that cause obesity problems. As a solution, calorie deficit was chosen as a program to solve this obesity problem. Developed an application called "Calcraft" which is integrated with a recommendation system to provide food selection recommendations by considering the calculation of BMI (Body Mass Index) and BMR (Basal Metabolic Rate). Application evaluation is carried out using the System Usability Scale (SUS) method, with a focus on user interface and user experience. Not only that, but the user’s understanding of the knowledge also gained from the features on Calcraft is one of the things the author hopes for. Of the 35 respondents who filled out the SUS questionnaire, "Calcraft" obtained a total score of 2907.5, with an average of 83.07142857. These results indicate very good quality, corresponding to the "A" or "Excellent" category in SUS interpretation. Thus, this app has great potential to assist individuals in running a calorie deficit program effectively and conveniently.